Atom probe tomography of compositional fluctuation in GaInN layers. (5th April 2016) - Kanitani, Yuya; Tanaka, Shinji; Tomiya, Shigetaka; Ohkubo, Tadakatsu; Hono, Kazuhiro
Abstract: Thin Ga1− x In x N layers with various indium compositions x were examined by high-angle annular dark-field scanning transmission electron microscopy and atom probe tomography. Although nanoscale compositional fluctuation was observed in all Ga1− x In x N layers, no appreciable phase separation was observed. Since Ga1− x In x N layers were coherently grown on underlying GaN layers, it is considered that the elastic strain constrains phase separation in the Ga1− x In x N layers and that compositional fluctuations develop in order to minimize the local strain energy. The measured period of compositional fluctuations ranged from 3.4 to 4.9 nm and decreased with growth temperature ( T growth ). This tendency is suggested to be dominated by the surface migration length of the adatom during the crystal growth.